Mild Clinical Behaviour of Crohn Disease in Elderly Patients in a Latin American Country: A Case-Control Study - Jesús K Yamamoto-Furusho; Andrea Sarmiento-Aguilar (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Crohn disease is characterized by fluctuating clinical behaviour, which is influenced by various factors. There are no data from Latin America that evaluate the clinical behaviour of Crohn disease in elderly patients.